Trump’s advocacy of nationalism: A rhetorical analysis of selected speech - Rayamajhi, Shunil (Shanti Journal, 2023)
This paper examines the political persuasion strategies employed by Donald Trump in his speech at the United Nations General Assembly on September 24, 2019. The qualitative study explores the reality and authenticity behind Trump’s claim “nationalism, not globalism, promotes peace, prosperity and economic growth of a sovereign nation like the US”. He attempted to persuade American to work for the prosperity of a nation; not for globalism. The study analyzes the ways to project political ideologies of Trump through the propagation of self-presentation and political persuasion. As the world leader with enormous political power wielded by the US, Trump’s speech under reference provides valuable insights into the ways how rhetoric links with power. This paper focuses on Trump’s nationalism which he exploited to motivate the Americans being experience as the losers of globalization to give him their vote in the next election. Toulmin’s model of sound argumentation has been employed as the qualitative interpretative method in the study to analyze the rhetorical elements of political persuasion contained in the speech. Trump’s behavior and speeches are full of contradictions. He held the populist political agenda of anti-globalization to appear as a true nationalist leader amongst the working-class American voters who could contribute to re-elect him as the President of the USA. However, his political rhetoric did not work as the majority of American voters cast their votes against him in the 2020 Presidential election.